Role of Gandhi Ji in the Indian National Freedom Movement: Perceptions and Allegations Surrounding Gandhi Ji's Role in the Indian National Freedom Movement (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Gandhi Ji” recognised Indian National Congress as an instrument for the national struggle. He used Satyagraha as a new weapon for the national liberation. Muslim fundamentalist led by Jinna alleged that he was an ardent Hindu Similarly the Hindu Nationalist alleged that he was promoting Muslim communalism in the country and cited the example of khilafat movement which he supported The Marxist also alleged that Gandhi had a strong class bias in favour of rich. Dr Ambedkar Kansi Ram and other dalit leader’s leveled allegation that he was a true representative of Savrala Hindu and he worked for their hegemony over the Avarena sections of the Hindus more particularly even the dalites.